고등학생의 정신건강 및 문제행동에 영향을 미치는 요인: 사회인지진로이론에 근거하여 - 손해경; 이혜정; 김미영; Son, Hae Kyoung; Lee, Hyejung; Kim, Miyoung (Child health nursing research, 2014)
Purpose: This study was conducted to identify factors affecting mental health and behavioral problems among high school students through the lens of a Social Cognitive Career Theory. Methods: A descriptive study was carried out with 384 high school students in Seoul, Korea. A self-administrative questionnaire was used. It consisted of items on person background variables, career-related variables including career barriers, learning experiences, self-efficacy, outcome expectations, and career indecision, and mental health and behavioral problems. Descriptive statistics, correlation analysis and multiple regression analysis were performed using the SPSS 21.0 program. Results: The results showed that perceived stress (t=5.12, p<.001), perceived health status (t=-4.08, p=.002), and school record (t=5.46, p<.001) were statistically significant variables. Also, career barriers (t=10.57, p<.001) was a significant factor influencing mental health and behavioral problems. Conclusion: These findings indicate that among career-related variables, career barrier needs to be considered for preventive and therapeutic approach to mental health and behavioral problems in adolescents. Furthermore, the results suggest that career-related stress level should be assessed in high school students on a regular basis. 목적 본 연구는 사회인지진로이론에 입각하여 우리나라 고등학생의 정신 건강 및 문제행동에 영향을 미치는 요인을 규명하기 위해 수행되었다. 방법 본 연구는 2013년 11월 18일부터 29일까지, S시에 소재한 인문계 고등학교 재학생 384명(남자 186명, 여자 198명)을 대상으로 한 서술적 조사연구이다. 연구도구는 개인 배경 변인, 진로 관련 변인(진로장벽, 학습경험, 자기효능감, 결과기대, 진로미결정), 정신건강 및 문제행동에 관한 자기기입식 설문지였으며 수집된 자료는 SPSS 21.0 프로그램을 활용하여 기술통계, 상관관계 및 다중 회귀분석을 하였다. 결과 다중 회귀분석 결과, 개인적 변인으로 스트레스 인지(t=5.12, p < .001)와 평상시 건강상태(t=-4.08, p <.001), 배경적 변인으로 학업성적(t=5.46, p <.001), 진로 관련 변인에서 진로장벽(t=10.57, p <.001)이 정신 건강 및 문제행동에 유의미한 영향을 미치는 요인으로 나타났다. 결론 고등학생의 정신건강 및 문제행동의 영향요인으로 개인 배경 변인과 함께 진로장벽을 확인하였다. 특히, 진로결정은 발달과정 동안 지속적으로 영향을 받으므로 진로를 선택하는 청소년 후기에 이를 고려한 예방적, 중재적 접근이 필요하다. 본 연구결과를 토대로 청소년의 정신 건강 및 문제행동 수준을 개선하기 위한 중재 개발과 학교보건 및 실무에의 적용에 기초자료로 활용될 것을 기대한다.